The Effect of Bifilm and Sr Modification on the Mechanical Properties of AlSi12Fe Alloy - Uludağ, M.; Gurtaran, M.; Dispinar, D. (Polish Academy of Sciences Chancellery, 2020)
The microstructure of Al-Si alloy has coarse silicon and this structure is known dangerous for mechanical properties due to its crack effect. Sr addition is preferred to modify the coarse silica during solidification. Additionally, bifilms (oxide structure) are known as a more dangerous defect which is frequently seen in light alloys. It is aimed at that negative effect of bifilms on the properties of the alloys tried to be removed by the degassing process and to regulate the microstructure of the alloy. In this study, the effect of degassing and Sr modification on the mechanical properties of AlSi12Fe alloy was investigated, extensively. Four different parameters (as-received, as-received + degassing, Sr addition, Sr addition + degassing) were studied under the same conditions environmentally. The microstructural analyses and mechanical tests were done on cast parts. All data obtained from the experimental study were analyzed statistically by using statistical analysis software. It was concluded from the results that Sr addition is very dangerous for AlSi12Fe alloy. It can be suggested that to reach high mechanical properties and low casting defects, the degassing process must be applied to all castings whereas Sr addition should not be preferred.
Keywords: Innovative foundry technologies and materials; AlSi12Fe alloy; Mechanical properties; Bifilm index; Sr modification